Preliminary Results on the Seasonal Size Distribution of Mytilicola orientalis and the Effect of this Parasite on the Condition of the Pacific Oyster, Crassostrea gigas - Chew, K. K.; Sparks, A. K.; Katkansky, S. C. (Journal of the Fisheries Research Board of Canada, 1965)
not available